Jalan Gender, Jalan Spiritual: Menggali Pembentukan Gender Project dalam Konteks Pengalaman Keberagamaan Perempuan - Bandel, Katrin; Shakka, Anne; Linda, Gusnita; Ardhiani, Yustina Devi (Paradigma: Jurnal Kajian Budaya, 2021)
Using the method of collaborative autoethnography, this study critically reflects on the life stories of three women from different backgrounds by focusing on gender and religion. One of the main aspects that we examined is gender projects, i.e. the projections people make when imagining their future gender roles and identities. As a result of our (self-) observations, we found that, while at first the gender project of those women was formed by the patriarchal gender order of their society, as time progresses, after living through and evaluating a variety of often traumatic experiences, they developed their own gender projects more independently from the constraints of the society. Religion played double roles during this process. Sometimes religious institutions became the space where traumatic experiences occurred and were even promoted, while in other contexts, religious institutions were experienced as safe spaces. However, their personal spirituality and self-transformation tended to be nurtured outside of formal religious institutions. In the end, the evaluation of these plural and complex experiences led us to more awareness of the limitations of religious institutions in accommodating and supporting women’s spirituality, due to their patriarchal gender regimes.